Effect of Free Float and Volatility on Stock Liquidity in Indonesia Stock Exchange - VIRATAMA, Dimaz Irja; HASNAWATI, Sri; HENDRAWATI, Ernie (PT Keberlanjutan Strategis Indonesia, 2024)
Liquidity is one of the important things in investing in the stock market. The Indonesia Stock Exchange as a regulator makes and establishes regulations in the capital market to conduct trading in an orderly, fair and efficient manner. One of the amended provisions in the regulation is regarding the free float or the percentage of the number of shares outstanding in the public with the aim of increasing the liquidity of the listed shares. In addition to free float, the risk in investing also needs to be considered. Behind a high return there is a high risk as well. High risk in the volatility of stock returns. High volatility attracts investors to invest in the stock market. Investors with risk-taking tendencies prefer this high-volatility condition because it allows them to earn higher returns, thereby increasing liquidity through the trading volume of these shares. This study involves a number of control variables that together determine market liquidity, namely Stock Return, Firm Size and Stock Price. The analysis was carried out on property and construction sector companies listed in the 2016-2020 period. The analytical method used is multiple linear regression analysis using the E-Views 10 application. The results of the analysis found that free float and volatility have a positive effect on stock liquidity, either by including or including control variables. These results indicate that information about free float and volatility is a consideration in capital market investment decisions